Dampak Korupsi Terhadap Pertumbuhan Ekonomi: Studi Kasus 4 Negara di ASEAN - Akhmad Faisal Lutfi; Zainuri Zainuri; Herman Cahyo Diartho (UPT Penerbitan Universitas Jember, 2020)
Today the phenomenon of the influence of corruption to economic growth has been a fairly hot issue of debate, both theoretically and empirically. The research uses a data panel analysis with a Random Effect Model approach to determine if corruption has a negative impact on economic growth in 4 ASEAN countries over the period of 2004-2015. Analysis results show that variable corruption has a negative influence on economic growth despite being insignificant, while other variables that have a significant positive influence on economic growth are public investments. The results of this study confirm that the negative effects of corruption do not directly affect economic growth but rather lead to the inefficiencies of production processes and the misallocation of resources.